2021
DOI: 10.1007/s41782-021-00127-7
|View full text |Cite
|
Sign up to set email alerts
|

Battery Discharge from Monday to Friday: Background Social Stress at Work is Associated with more Rapid Accumulation of Fatigue

Abstract: Purpose This field study investigated the effects of background social stress at work on the weekly course of evening fatigue. Methods Male employees of a Swiss organisation reported their fatigue after work and at 9 pm in the evening over three weeks. A total of 482 evening fatigue measurements from 34 male participants were subjected to multilevel analysis. Results Sleep quality in the previous night and fatigue a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…This variable is "1" for Monday, "2" for Tuesday and so on, till "5" for Friday. A recent study has confirmed that across weekdays, employees' fatigue may vary (Elfering et al, 2021).…”
Section: Daymentioning
confidence: 87%
“…This variable is "1" for Monday, "2" for Tuesday and so on, till "5" for Friday. A recent study has confirmed that across weekdays, employees' fatigue may vary (Elfering et al, 2021).…”
Section: Daymentioning
confidence: 87%
“…This finding is consistent with the study by Riley et al, which reported a decline in cognitive and attentional abilities in the afternoon and a corresponding increase in errors throughout the day [ 28 ]. Although employees may partially recover from mental fatigue and stress from mental detachment, such as exercise and sleep in the evening, previous studies have shown that this recovery is limited, and their mental resources do not fully restore, accumulating over the workweek [ 29 ]. As a result, employees report higher levels of mental fatigue, stress, and negative mood on Thursdays and Fridays, compared to Mondays and Tuesdays [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both high daily workload (NPR) and high cumulative workload (ACDW) act as stressors, leading to a modulation effect of NPR on ACDW. Elfering et al (2021) have shown that fatigue increases with consecutive working days but accumulates faster at higher levels of daily…”
Section: Interaction Of the Number Of Consecutive Working Days With S...mentioning
confidence: 99%